Emmanuel Macron and the reprojection of the French language. - Ahearne, Jeremy (Modern & Contemporary France, 2022)
Although preceding presidents of the Fifth Republic have shown commitment in varying degrees to the projection of the French language, none has done so in as focused and symbolically charged a manner as Emmanuel Macron. This can be explained through the combination of his individual biographical trajectory, the opportunity offered to carve out a presidential profile in relation to his predecessors and his rivals, and through the contemporary position of French in the world language system. The uncertain position of French in this system means that Macron could not simply perpetuate older rhetorical and policy practices for projecting the language. Instead he sought to recast French as an imaginary object through recourse to an alternative cluster of metaphors and a reframed symbolic space, and the appropriation of motifs developed by postcolonial and other critical thinkers. He also aggregated a platform of policy measures acting as 'semes' designed to demonstrate the uses and desirability of the language under the rubrics of education, communication and creation. Macron's reprojection of French is 'versatile' and ambiguous insofar as it allows him symbolically to defuse political and cultural tensions. This is demonstrated in his project for a Cité internationale de la langue française in Villers-Cotterêts.